Penerapan Akuntansi Syariah dalam Jual Beli Online (E-Commerce) - Muammar Khaddafi; Nurhaliza Nurhaliza; Ardiansyah Ardiansyah; Nazwa Nabila; Selvisah Pitriyani; Eka Yanti (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
With the development of technology today, there are various methods to conduct buying and selling transactions. One of them is electronic buying and selling or E-Commerce. And with us doing this online buying and selling transaction, whether the transaction has been carried out in accordance with the rules of islamic accounting. How can the provisions of islamic accounting be applied to the online buying and selling system. One of the ways to trade in islamic is by doing a contract, therefore we see whether this way of trading can be applied to online buying and selling.